2014
DOI: 10.4238/2014.april.16.10
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Development and characterization of novel transcriptome-derived microsatellites for genetic analysis of persimmon

Abstract: ABSTRACT. Oriental persimmon (Diospyros kaki Thunb.) (2n = 6x = 90) is a major commercial and deciduous fruit tree that is believed to have originated in China. However, rare transcriptomic and genomic information on persimmon is available. Using Roche 454 sequencing technology, the transcriptome from RNA of the flowers of D. kaki was analyzed. A total of 1,250,893 reads were generated and 83,898 unigenes were assembled. A total of 42,711 SSR loci were identified from 23,494 unigenes and 289 polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…Moreover, 100 SSRs were selected to design the EST-SSR primers (Table 6 and Additional file 11: Table S7) from 2603 single copy orthogroups shared in nine samples, and 66% products exhibited more than one band in all nine samples. Our PCR success rate was higher than that in a previous study [40], but it was slightly lower than those reported in rubber [42]. The failure of 34 primer pairs to produce amplicons may be due to the location of the primers across the splice sites, chimeric primers, poor-quality sequences, or the high heterozygosity.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Moreover, 100 SSRs were selected to design the EST-SSR primers (Table 6 and Additional file 11: Table S7) from 2603 single copy orthogroups shared in nine samples, and 66% products exhibited more than one band in all nine samples. Our PCR success rate was higher than that in a previous study [40], but it was slightly lower than those reported in rubber [42]. The failure of 34 primer pairs to produce amplicons may be due to the location of the primers across the splice sites, chimeric primers, poor-quality sequences, or the high heterozygosity.…”
Section: Discussioncontrasting
confidence: 69%
“…The development of the SSRs in the genus Diospyros was mostly focused on the DK species using the traditional enriched genomic library [39]. Recently, it was reported that 42,711 SSR loci were found using Roche 454 sequencing technology, and 98 revealed polymorphisms between 15 DK genotypes [40]. However, some closely related species with DK still lack the SSR information.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 218 pairs of primers showed stable PCR amplification with products of the expected sizes; 93 pairs of primers identified polymorphisms in the 7 mango genotypes ( Table S1). The rate of polymorphism in mangoes (43.12%) was lower than the 64.7% reported in oak (Torre et al, 2014), 63.23% in persimmon (Luo et al, 2014), and 46.5% in field pea (Kaur et al, 2012), but higher than the 21.2% in Asian lotus (Zhang et al, 2014a), 27.3% in cotton (Zhang et al, 2014b), and 36% in tea (Wu et al, 2013). The sequences of the 93 pairs of primers that identified polymorphisms and the characteristics of their amplification products are given in Table S1.…”
Section: Resultsmentioning
confidence: 90%
“…Using Roche 454 sequencing technology, the transcriptome from RNA of the flowers of D. kaki was analyzed (Luo et al, 2014). Using Roche 454 sequencing technology, the transcriptome from RNA of the flowers of D. kaki was analyzed (Luo et al, 2014).…”
Section: Flowermentioning
confidence: 99%